BEHAVIOR OF PARENTS IN ADOLESCENTS WHO HAVE UNWANTED PREGNANCY : LITERATURE REVIEW - Ermiati Ermiati; Agfa Ramadhany Munggaran; Altia Nurrohmah; Neng Ikhtiyarotul Fikriyah; Risma Indriyani; Andinita Siti Maulidah (Ikatan Perawat Maternitas Indonesia Provinsi Jawa Barat, 2021)
Unwanted Pregnancy in adolescents increases every year and raises rejection, exclusion, and even expulsion towards adolescents both by family and society. Meanwhile, adolescents who go through unwanted pregnancies need their families accompany and protect them. Objective: This literature aims to examine parents’ behavior towards adolescents who experience unwanted pregnancies. Method: Literature review using keywords in Indonesian and English. The keywords in Indonesian were